REDESAIN TERMINAL BIS KEDAMIN - Wardhana, Anfasa Teguh; Putro, Jawas Dwijo; Alhamdani, Muhammad Ridha (JMARS: Jurnal Mosaik Arsitektur, 2021)
Transportation is the activity of moving an individual or group and tools or goods from one place to another. There are 3 types of transportation: land, water and air. Transportation by type is grouped into private transportation and public transportation. In Kapuas Hulu there are 6 Bus Terminals, one of which is the Type B Bus Terminal in Kedamin which is the highest type bus terminal in Kapuas Hulu. For the Type B Bus Terminal, the Kedamin Terminal has not met the requirements stipulated in government regulations, so it is necessary to redesign it to meet the standard for the Type B terminal. Bus terminals that look dirty are due to the unloading and loading activities that are not in place so that it disturbs the comfort of bus terminal visitors. Supporting facilities for bus management activities is inadequate. Insufficient arrival and departure waiting areas. Activities on a regular basis are disrupting the circulation of vehicles, therefore it is necessary to redesign the Kedamin Bus Terminal. The Bus Terminal design applies a contextual concept to adapt the conditions of the building on site to the surrounding conditions.